Winner takes all: the challenges and opportunities in the study tour industry in China after the epidemic - Longyue, Cheng; Abdul Aziz, Nor Akmar; Ai Lin, Evelyn Lim; Liya, Yu (Human Resources Management Academic Research Society (HRMARS), 2024)
As a branch of educational tourism, study tours continue to develop globally, and China has also begun to encourage the development of study tours since 2016. This emerging market has attracted tourism companies seeking new business opportunities, tourism companies have perceived study tours as a new industry opportunity. However, the anticipated profitability of study tours has not always materialized. This research investigates the current state of the study tour market in China, focusing on corporate profitability and tourism safety issues. The study reveals that while a few companies manage to achieve profitability, most struggle to break even. Key challenges include high operational costs, regulatory hurdles, and safety concerns. The findings suggest that the market operates on a "winner takes all" principle, where only a small number of firms succeed, raising questions about the long-term sustainability and attractiveness of the study tour business in China.